2006
DOI: 10.1038/sj.embor.7400858
|View full text |Cite
|
Sign up to set email alerts
|

The supramolecular architecture of junctional microdomains in native lens membranes

Abstract: Gap junctions formed by connexons and thin junctions formed by lens-specific aquaporin 0 (AQP0) mediate the tight packing of fibre cells necessary for lens transparency. Gap junctions conduct water, ions and metabolites between cells, whereas junctional AQP0 seems to be involved in cell adhesion. High-resolution atomic force microscopy (AFM) showed the supramolecular organization of these proteins in native lens core membranes, in which AQP0 forms two-dimensional arrays that are surrounded by densely packed ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
115
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 28 publications
5
115
1
Order By: Relevance
“…NATURE COMMUNICATIONS | DOI: 10.1038/ncomms3155 ARTICLE membranes by AFM [16][17][18] , they have not been observed on native cells in physiological buffer. Beyond structural aspects, questions remain unanswered concerning the dynamics of junctional microdomains, notably in the context of assuring cell adhesion during tissue deformation upon lens accommodation (focusing to different distances).…”
Section: Development Of Hybrid Hs-afm and Fluorescence Microscopementioning
confidence: 98%
See 1 more Smart Citation
“…NATURE COMMUNICATIONS | DOI: 10.1038/ncomms3155 ARTICLE membranes by AFM [16][17][18] , they have not been observed on native cells in physiological buffer. Beyond structural aspects, questions remain unanswered concerning the dynamics of junctional microdomains, notably in the context of assuring cell adhesion during tissue deformation upon lens accommodation (focusing to different distances).…”
Section: Development Of Hybrid Hs-afm and Fluorescence Microscopementioning
confidence: 98%
“…For comparison, in conventional AFM setups, the impulse is about three orders of magnitude higher. We can identify AQP0 by the characteristic square array packing in lens cells, previously described by freeze fracture electron microscopy 15 and by AFM of isolated membranes [16][17][18] , with packing parameters of a ¼ b ¼ 6.5 nm, g ¼ 90° (Fig. 5a).…”
Section: Development Of Hybrid Hs-afm and Fluorescence Microscopementioning
confidence: 99%
“…Recent x-ray and electron-diffraction structures have shown that AQP0 can exist both as a nonjunctional homotetramer (17), in which each monomer transports water, and as a junctional octamer formed by hydrophobic interactions between two tetramers juxtaposed headto-head in adjacent membranes (11,13,19,22). The conductance of the junctional form has been debated (11,17,19,20,22); it has been suggested that AQP0, in its junctional form, is nonconducting (11,19), but the differences between the structure of this form and that of the conducting, nonjunctional form seem minor (17). Junction formation has been associated with proteolytic cleavage of the C-terminus of AQP0 (11), but experimental evidence suggests that the cleaved form conducts water when not engaged in junction formation (23).…”
mentioning
confidence: 99%
“…By contrast, the AQP0 structure was determined to a resolution of 1.9 Å using 2D crystals produced by reconstituting delipidated protein with the synthetically made lipid dimyrostylphosphatidylcholine (DMPC). Since the double-layered 2D crystals have the same dimensions as AQP0-mediated membrane junctions between fiber cells in the lens [10], the synthetic DMPC lipid is likely to mimic the native lipids in the in vivo junctions [8]. The lipids in the 2D crystals form an almost complete bilayer and are sandwiched in between adjacent AQP0 tetramers.…”
Section: Introductionmentioning
confidence: 99%